PENGARUH INTERNATIONALIZATION TERHADAP IPO PERFORMANCE DENGAN FOUNDER’S ROLE SEBAGAI MODERASI PADA PERUSAHAAN IPO TAHUN 2017-2021 - Meilina, Vera; Imelda, Elsa (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to show how firm size, firm age, hot market and internationalization affect IPO underpricing on listed company in Bursa Efek Indonesia (BEI) during 2017-2021. Sample was selected using disproportionate stratified random sampling method and the valid data was 79 companies. The Data is processed using multiple regression analysis method with SPSS program (Statistical Package for the Social Sciences) version 25 released on Windows and Microsoft Excel 2010. The result of this study indicate that internationalization have no significant effect on IPO underpricing and adding moderating variable will not affect the significance of internationalization on IPO underpricing on a company with founder CEO, and strengthen the effect of internationalization on IPO underpricing on a company with non-founder CEO. This implies that non-founder CEO will bring a more positive signal to the company, because non-founder CEO will enhance management in more complex and bigger company.